Reproductive biology of Bowdichia virgilioides Kunth (Fabaceae) - doi: 10.4025/actascibiolsci.v33i4.9003 (Acta Scientiarum. Biological Sciences, 2011)
The aim of this study was to investigate the reproductive biology of Bowdichia virgilioides in an area of Cerrado (Brazilian Savanna). The study was carried out in Chapadinha, State of Maranhão in northeastern Brazil. Bowdichia virgilioides has cornucopia flowering and annual pattern. Flowering occurred at the beginning of the dry season, between June and August; and fruiting in the middle of this season, between July and October. The anthesis of B. virgilioides is diurnal, and the main flower resource is the nectar. During the flower opening, the anthers becomes dehiscent and thus pollen grains are deposited at the stigma, promoting automatic self-pollination. The species is self-compatible and apomitic. In the study area, they were visited by nine species of bees, four butterflies, two wasps, and two hummingbirds. The visits began in early morning and persisted throughout the day, with a peak of activity between 8:00 and 9:00 hours. Species of Centris were the main visitors of B. virgilioides. The butterfly and wasp species were considered resource robbers, and other floral visitors were considered occasional visitors. Although the flowers of B. virgilioides are widely visited, the species shows a high rate of inbreeding because of automatic self-pollination.